Serum metabolomics characteristics and fatty-acid-related mechanism of cirrhosis with histological response in chronic hepatitis B - Fan, Hai-Na; Zhao, Zhi-Min; Huang, Kai; Wang, Xiao-Ning; Dai, Yun-Kai; Liu, Cheng-Hai (Frontiers in Pharmacology, 2023)
Background and aims: The serum metabolites changes in patients with hepatitis B virus (HBV)-related cirrhosis as progression. Peroxisome proliferator-activated receptor gamma (PPARγ) is closely related to lipid metabolism in cirrhotic liver. However, the relationship between fatty acids and the expression of hepatic PPARγ during cirrhosis regression remains unknown. In this study, we explored the serum metabolic characteristics and expression of PPARγ in patients with histological response to treatment with entecavir. Methods: Sixty patients with HBV-related cirrhosis were selected as the training cohort and were equally divided into regression (R) and non-regression (NR) groups following pathological changes after 48-week treatment with entecavir. Another 72 patients with HBV-related cirrhosis also treated with entecavir were included in the validation cohort. All of the serum samples were tested using ultra-performance liquid chromatography coupled to tandem mass spectrometry. Data were processed through principal component analysis and orthogonal partial least square discriminant analysis. Hepatic PPARγ expression was observed using immunohistochemistry. The relationship between serum fatty acids and PPARγ was calculated using Pearson’s or Spearman’s correlation analysis. Results: A total of 189 metabolites were identified and 13 differential metabolites were screened. Compared to the NR group, the serum level of fatty acids was higher in the R group. At baseline, the expression of PPARγ in hepatic stellate cells (HSCs) was positively correlated with adrenic acid (r2 = 0.451, P = 0.046). The expression of PPARγ in both groups increased after treatment, and the expression of PPARγ in the R group was restored in HSCs much more than that in the NR group (P = 0.042). The adrenic acid and arachidonic acid (AA) in the R group also upgraded more than the NR group after treatment (P = 0.037 and 0.014). Conclusion: Baseline serum differential metabolites, especially fatty acids, were identified in patients with HBV-related cirrhosis patients who achieved cirrhosis regression. Upregulation of adrenic acid and AA in serum and re-expression of PPARγ in HSCs may play a crucial role in liver fibrosis improvement.